Microtia and congenital atresia of the external auditory canal: a case report - Gomes, Pedro (2024)
Microtia and congenital atresia of the external auditory canal (EAC) are congenital malformations of the external ear that are often associated. Microtia results from a malformation of the auricle, while congenital atresia is a total or partial occlusion of the EAC. The challenge for the otolaryngologist is the management, which may include reconstructive surgery and auditory rehabilitation. Each case is unique and requires an individualized approach by a specialized team of otolaryngologists and plastic surgeons. We present the case of a 62-year-old woman with microtia and congenital atresia of the right EAC, with a history of reconstructive surgery of the pinna, in which auditory rehabilitation with an osseointegrated implant was chosen.